Australian elite juniors' perceptions of the importance of mental skills - Young, J. A. (Medicine and Science in Tennis, 2008)
Elite junior tennis players` perceptions of the importance of mental skills were investigated in a study commissioned by Tennis Victoria. Eight junior boys aged 13 to 17 years and seven girls aged 12 to16 years comprising an elite training squad at Melbourne Park responded to a questionnaire. Reponses to ratings of the importance of mental and physical factors, and key mental skills for success were recorded, together with the time devoted to mental preparation prior to important matches and explanations for match losses. While mental factors and skills were strongly endorsed, no gender differences were found in these endorsements or in the time devoted to mental preparation. Losses in important matches were generally attributed to mental factors. Results were interpreted in terms of the maturity of players and shared exposure to the State coach`s training methods and program. Future directions in tennis mental skills research are highlighted.